Oral calcium supplementation versus placebo in mitigating citrate reactions during apheresis: an open-label randomized control trial - Masaya Abe; Keiko Fujii; Nobuharu Fujii; Toshiharu Mitsuhashi; Takuya Fukumi; Yuichi Sumii; Maiko Kimura; Tomohiro Urata; Takumi Kondo; Fumio Otsuka; Yoshinobu Maeda (Hematology, Transfusion and Cell Therapy)
Background: Citrate-related hypocalcemia is the most common adverse event linked with peripheral blood progenitor cell apheresis. A previous retrospective study highlighted the prophylactic effectiveness of oral calcium drinks before apheresis, supplemented with intravenous calcium gluconate. Consequently, this study is a randomized controlled trial comparing oral calcium with placebo drinks Study Design and Methods: Healthy donors were randomized to receive either oral calcium (Cohort A) or placebo (Cohort B) drinks. If symptoms emerged, all donors were given calcium drinks to counteract hypocalcemia. The primary endpoint centered on the incidence of Grade 1 or higher citrate-related symptoms. Analyses were performed using the crude model and doubly robust estimation. Results: Forty-two healthy donors participated from January 2021 to July 2022. Case distribution (Cohort A: Cohort B) stood at 3:7 (Grade 1), 2:2 (Grade 2), and 1:0 (Grade 3); no Grade 4 cases were identified. There was no statistical significance in the incidence of Grade 1 or higher and Grade 3 citrate-related symptoms. Discussion: The cumulative incidence of citrate-related side effects was less pronounced than in the previous research. This could stem from absence of blinding, and the decision to administer calcium drinks to the untreated group upon symptom detection. Although preemptive oral calcium intake before peripheral blood progenitor cell apheresis is not wholly effective, providing calcium-rich beverages to symptomatic donors may stave off symptom intensification.